2017
DOI: 10.3390/ijms18071439
|View full text |Cite
|
Sign up to set email alerts
|

Abnormally Increased Secretion in Olfactory Neuronal Precursors from a Case of Schizophrenia Is Modulated by Melatonin: A Pilot Study

Abstract: The alterations that underlie the pathophysiology of schizophrenia (SCZ) include the dysregulation of structural and functional properties of neurons. Among these, the secretion of neurotransmitters and hormones, which plays a key role for neuronal communication and development, is altered. Neuronal precursors from the human olfactory epithelium have been recently characterized as a reliable model for studying the etiopathogenesis of neuropsychiatric diseases. Our previous work has shown that melatonin enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Induction of seizures to a rat mother led to early embryonic neurogenesis and delayed maturation of newborn neurons in the cerebellum and the Cornus ammonis 1 (CA1) region of the hippocampus in PND0 offspring [ 114 , 115 ]. Olfactory NSCs isolated from schizophrenia (SCZ) patients also exhibited an abnormal increase in the potassium-evoked secretion when compared with the NSCs of the healthy control [ 116 ]. Interestingly, melatonin treatment could reverse all the abnormalities caused by seizures [ 114 , 115 , 116 ] ( Table 12 and Table 13 ).…”
Section: Melatonin and Other Diseases That Are Related To Neurogenmentioning
confidence: 99%
See 1 more Smart Citation
“…Induction of seizures to a rat mother led to early embryonic neurogenesis and delayed maturation of newborn neurons in the cerebellum and the Cornus ammonis 1 (CA1) region of the hippocampus in PND0 offspring [ 114 , 115 ]. Olfactory NSCs isolated from schizophrenia (SCZ) patients also exhibited an abnormal increase in the potassium-evoked secretion when compared with the NSCs of the healthy control [ 116 ]. Interestingly, melatonin treatment could reverse all the abnormalities caused by seizures [ 114 , 115 , 116 ] ( Table 12 and Table 13 ).…”
Section: Melatonin and Other Diseases That Are Related To Neurogenmentioning
confidence: 99%
“…Olfactory NSCs isolated from schizophrenia (SCZ) patients also exhibited an abnormal increase in the potassium-evoked secretion when compared with the NSCs of the healthy control [ 116 ]. Interestingly, melatonin treatment could reverse all the abnormalities caused by seizures [ 114 , 115 , 116 ] ( Table 12 and Table 13 ).…”
Section: Melatonin and Other Diseases That Are Related To Neurogenmentioning
confidence: 99%
“…The culture of stem cells obtained from the human olfactory epithelium (hOE) had enabled the study of diverse cellular processes that are dependent on Ca 2+ signaling in neuronal cells, for instance, the olfactory transduction in sensory neurons [12], axonogenesis [13, 14], exocytosis triggered by depolarization of the plasma membrane [15], and microtubule organization [16]. Therefore, this cell culture could be an ex vivo suitable model to study the Ca 2+ -dependent mechanisms underlying proliferation [17], migration [18], or differentiation [19] in neuronal precursor cells.…”
Section: Introductionmentioning
confidence: 99%
“…There is experimental evidence that neural cells obtained in vitro from explants of olfactory mucosa may be used for regenerative purposes (11,12,14,(19)(20)(21)(22). Recent evidence has shown that human olfactory mucosa stromal cells (SC) may offer unique properties as a peripheral reporter in some neuropsychiatric disorders (23)(24)(25)(26)(27) and chronical diseases such as Alzheimer's (28,29) and Parkinson (30).…”
mentioning
confidence: 99%